2011
DOI: 10.1007/s12034-011-0229-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oil and oil with graphite on tribological properties of glass filled PTFE polymer composites

Abstract: Present work deals with the experimental investigation of tribological properties of GF-filled polymer composites considering three velocities, i.e. 0⋅5, 1 and 2⋅0 m/s and loads ranging from 15⋅7 N to 45⋅13 N keeping rest of the parameters constant. The test has been carried out for three materials, PTFE + 15% GF, PTFE + 25% GF and PTFE + 35% GF in wet (oil) and adding additive as graphite (5% wt) in oil. SAE 20W40 oil is used for the test. Friction and wear tests of PTFE composite against a counter surface of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…These two distinctive peaks indicated that crosslinked structures were formed owing to tribochemical reactions during the wear of PTFE/NC composites. [20][21][22]24 These results showed that the adding of relatively small amounts (~2 wt %) of NC particles significantly changed the intensity of tribochemical processes and resulted in significant reduction of wear. Table 1 summarized the mechanical and tribomechanical characteristics of the neat PTFE and composites.…”
Section: -23mentioning
confidence: 95%
“…These two distinctive peaks indicated that crosslinked structures were formed owing to tribochemical reactions during the wear of PTFE/NC composites. [20][21][22]24 These results showed that the adding of relatively small amounts (~2 wt %) of NC particles significantly changed the intensity of tribochemical processes and resulted in significant reduction of wear. Table 1 summarized the mechanical and tribomechanical characteristics of the neat PTFE and composites.…”
Section: -23mentioning
confidence: 95%
“…Glass fiber and Bronze can also be used as a filler material in PTFE which also may lead to improvement in wear resistance [13]. Addition of glass fiber in PTFE under wet condition, also improves the wear performance of PTFE material under different varying condition like load, velocity and sliding distance [14].…”
Section: A Ptfe As a Bearing Materialsmentioning
confidence: 99%
“…PTFE increases with glass fiber fillers and composites have good friction and wear behavior at higher speeds, so it can be more effectively used for high speed applications. Also the wear of the PTFE composites can be decreased by using oil and oil with graphite lubrication [11]. Shanta, et.al (2011) conducted their experiments on mixtures of SAE 15W40 oil, which were contaminated by known percentages of the bio diesels from canola oil, peanut oil, soybean oil, The friction behavior and where property were studied by means of pin-on -disc tribometer test were carried under wet conditions (Hydrodynamic lubrication) where the pin is AISI 316 stainless steel and the disc is AISI 1018 with a mixture of oils.…”
Section: Introductionmentioning
confidence: 99%